Changes in food bolus texture during mastication. Issue 2 (12th September 2016) - Wada, Sachie; Goto, Takaharu; Fujimoto, Keiko; Watanabe, Megumi; Nagao, Kan; Nakamichi, Atsuko; Ichikawa, Tetsuo
Abstract: The purpose of this study was to survey the changes that occur in bolus texture from intake to swallowing during the mastication process for four types of food materials and to identify how texture is related to the number of chews. We recruited 15 young Japanese participants for this study. The subjects were asked to spit the food bolus just before swallowing when eating four different foods: cracker, boiled rice, hard gelatine gel, and soft gelatine gel. Three physical properties (hardness, adhesiveness, and cohesiveness) were measured in the bolus after being chewed for 25, 50, 75, 100, and 125% of the normal number of chews. Occlusal force and pressure as well as stimulated whole saliva volume were also measured. Extensive variation in the number of chews existed between subjects, but minimal intra‐subject variation was observed. Hardness was observed to decrease, whereas cohesiveness and adhesiveness increased in a chew‐dependent manner for the cracker, soft gelatine gel, and hard gelatine gel, but not boiled rice. Bolus texture appears to be largely related to the number of chews. Hardness also tended to be influenced by occlusion. The adhesiveness and hardness of the boiled rice were also greatly influenced by saliva volume and occlusal force, respectively. Hardness is an important rheological factor in food bolus texture and likely plays a significant role in determining the appropriate number of chews. Adhesiveness and cohesiveness appear to be secondary factors in this process. Practical applications: We propose a model of oral processing for application in determining the appropriate number of chews for an individual. Hardness appears to be an important rheological factor in food bolus texture, with adhesiveness and cohesiveness being secondary aspects. When food is hard or difficult to swallow, chewing behavior will likely be more influenced by the perception of bolus texture.